2020
DOI: 10.3390/su12072612
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Collaborative Approaches for Service Provision to Low-Income Countries: Expert Panel Results

Abstract: The international development sector is increasingly implementing collaborative approaches that facilitate a range of sectoral-level stakeholders to jointly address complex problems facing sustainable public service delivery, for which guidance does not explicitly exist. The literature on collaborative approaches has been built on experiences in high-income countries with vastly different governance capabilities, limiting their global relevance. A Delphi expert panel addressed this need by evaluating 58 factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…This comparative analysis of CTCs in Global South countries contributes groundbreaking findings regarding collaborative counter-human trafficking efforts in nations outside of the relatively high income countries of the Global North—a vast realm in which there is a dearth of collaboration research (Pugel et al, 2020). Our findings evidence that the CTC’s leadership practices explain the positive, beneficial outcomes reported by coalition members as well as leaders.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This comparative analysis of CTCs in Global South countries contributes groundbreaking findings regarding collaborative counter-human trafficking efforts in nations outside of the relatively high income countries of the Global North—a vast realm in which there is a dearth of collaboration research (Pugel et al, 2020). Our findings evidence that the CTC’s leadership practices explain the positive, beneficial outcomes reported by coalition members as well as leaders.…”
Section: Discussionmentioning
confidence: 97%
“…Although existing literature addresses general aspects of leadership, according to Kramer et al (2019) there is a lack of grounded research on how collaboration leaders work with representatives of multiple organizations to achieve goals. Moreover, Pugel et al (2020) describe the Global North focus of most scholarship on collaboration, noting the “overwhelming need for (. .…”
Section: Rationale For the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the lack of published knowledge on government uptake may partially be due to the fact that virtually all theories and frameworks related to collaborative approaches (e.g. Ansell & Gash 2007;Gray & Purdy 2018) have been based on cases in high-income countries and non-development contexts, which experience very different governing regimes (Pugel et al 2020). Because existing theories insufficiently cover government uptake, strategies for how collaboratives can gain and maintain government uptake for their activities have likewise not been investigated in literature but are particularly relevant to the WASH sector.…”
Section: Collaborative Approaches Rely On Government Uptakementioning
confidence: 99%
“…These are more than typical partnerships more widely prevalent in the development sectora rigorous cross-case comparison of collaborative approaches in Eastern Africa found that some ways in which these approaches are different from typical partnerships and coordination platforms include establishing 'hub' organizations to lead and coordinate the effort, securing multiple years of funding for jointly implemented projects, bringing together the same set of stakeholders in quarterly meetings, and collectively identifying the problems they will address (Pugel et al 2021). The authors direct readers to a detailed review of literature on collaborative approaches in limited-governance and low-income contexts (Pugel et al 2020), which notes the dearth of rigorous research on collaborative approaches in low-and middle-income countries and development contexts.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%